(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article is intended to update the problems of managing the safe operation of objects of gas transportation as sources of technogenic and ecological danger, which is identified as one of the priority directions of development of NJSC «Naftogaz of Ukraine». The analysis of applied prerequisites for the use of economic expertise as a controlling instrument at the enterprises of the oil and gas industry of Ukraine has been carried out. The basic elements of the economic expertise concerning the projects of reconstruction, modernization and re-equipment of objects of the gas transportation system are determined. It is proved that the issue of determining and assessing the economic feasibility of incurred expenses for such measures is the subject of economic examination. The expediency of conducting it besides the obligatory departmental expertise was considered for ensuring completeness and objectivity in the part of both designing and direct reconstruction.